Synthesis of Ultra-High-Molecular-Weight Polyethylene by Transition-Metal-Catalyzed Precipitation Polymerization - Wang, Wenbing; Wang, Quan; Zou, Chen; Chen, Changle (Precision Chemistry, 2024)
Ultra-high-molecular-weight polyethylene (UHMWPE) plays an important role in many important fields as engineering plastics. In this contribution, a precipitation polymerization strategy is developed by combination of highly active phosphino-phenolate nickel catalysts with polymer-insoluble solvent (heptane) to access UHMWPE (M n up to 8.3 × 106 g mol–1) with good product morphology, free-flowing characteristics, and great mechanical properties. Compared with the academically commonly used aromatic solvent (toluene), the utilization of heptane offers simultaneous enhancement in important parameters including activity, polymer molecular weight, and catalyst thermal stability. This system can also generate polar functionalized UHMWPE with molecular weight of up to 1.6 × 106 g mol–1 in the copolymerization of ethylene with polar comonomers. More importantly, this precipitation polymerization strategy is generally applicable to several representative transition metal catalyst systems, leading to UHMWPE synthesis with good product morphology control.